Sentiment Analysis on Twitter Social Media towards Climate Change on Indonesia Using IndoBERT Model - Muhammad Fadhil Mubaraq; Warih Maharani (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
The phenomenon of climate change is a change in temperature and weather patterns in the long term. This incident became a frightening specter for everyone because consciously or unconsciously the bad effects of climate change are already in sight. This has become an urgency for all levels of society so that this topic has become quite hot on Social Media, especially on Twitter. The topic of climate change in Indonesia on Twitter Social Media can be analyzed so that it can be seen how people's sentiments towards this phenomenon. This research utilizes the Transformer architecture, namely IndoBERT, IndoBERT itself is the development of the BERT architecture by the IndoNLU team which has 74 million words from various Bahasa Indonesia sources. Therefore, this method was chosen in the hope of helping sentiment analysis on the topic of climate change so that public sentiment can be mapped. The test results obtained an F1-Score values of 95.6% with a tuning parameter of 0.00002 learning rate and 16 of batch size. Hopefully the results of this research can be used in future research.